Pembinaan Perilaku Sosial melalui Pengajian Rutin Kitab Akhlaq di Lingkungan RT 01 RW 12 Mimbaan Panji Situbondo - Moh. Fachri (GUYUB: Journal of Community Engagement, 2020)
People in RT01 RW02 Mimbaan Panji Situbondo and arounds as those who lived in urban area have got an impacts of modernisation and globalisation or—mostly known—‘modern sickness’. In their daily life, they have lack of attention into goodness or kind conducts, specially, based on religious values. Furthermore, moral teaching through daily recitation of kitab akhlak at RT01 RW02 Mimbaan Panji Situbondo intensively with  using some attractive methods and daily illustration is necessary and has an impact on the ways they are involved with that moral teaching.Keywords: RT01 RW02 Mimbaan Situbondo, Social Behavior, Daily Recitation